Psychiatry in Russia - Krasnov, V. N. (Die Psychiatrie, 2014)
Russian psychiatry has dramatic history, and till now is at a transitional stage of development. It is facing the problems not only common in world psychiatry, but also specific for the Eastern Europe, in particular for Russia. Starting from the beginning of 1990s considerable changes have occurred in psychiatry, especially after 1992 when “The law on psychiatric care and guarantees of citizens rights in its provision was adopted”. It became the ideological and legislative basis for reforms. However there are the definite obstacles for structural reforms in psychiatry. They are as follows: unfavourable technical conditions in many psychiatric clinics, hypercentralization of psychiatric services, shortage of clinical psychologists and social workers in psychiatry, some difficulties in cooperation between psychiatric and general medical institutions. Economic difficulties of the transition period of Russia’s social development prevent overcoming these problem. They are being actively discussed and part of them is being gradually solved, e.g. organization of team work in mental health services, increasing number of specialists on social work, involvement of NGO’s in psychosocial rehabilitation.
Keywords: Russian psychiatry; historical overview; legal and ethical problems; prevalence of mental disorders; resources and types of services; new trends